The formation of interests in psychology as a basis for the development of purposefulness among students of pedagogical specialities - Kregždė, A. (Psichologija, 1988)
The paper deals with the structure of interests at four levels dindifferent, consumer, spontaneous actor, and conscious actor ) in the psychology of students of pedagogical specialities. The interrelation between the student's interests in psychology and his interests in pedagogics referring to the empirical data is revealed. A sketch for differential formation of interests in psychology during experimental studies in general psychology is suggested.
Keywords: students of Pedagogical Specialities; Interests in Psychology; professional interests